Disseminated -Intracellulare Complex Infection Presenting With Disseminated Intravascular Coagulation in an AIDS Patient - Folusakin Ayoade MD; James Cotelingam MD; Andrew Stevenson Joel Chandranesan MD (SAGE Publishing, 2017)
Disseminated Mycobacterium avium -intracellulare complex (MAC) infection is one of the relatively common opportunistic infections seen in severely immunocompromised AIDS patients. A constellation of clinical, laboratory, and pathological features involving multiple organ systems are often present in disseminated MAC infection but disseminated intravascular coagulation (DIC) has not been previously described in association with this condition. To our knowledge, this is the first reported case of DIC complicating disseminated MAC infection in an AIDS patient. In this article, we present the case of a 33-year-old AIDS patient with high viral load, CD4 lymphocyte count of 1/mm 3 , who presented with nonspecific symptoms, anemia, thrombocytopenia, and increased lactate dehydrogenase, alkaline phosphatase, and ferritin. She also had abnormal coagulation parameters and features compatible with chronic DIC. Bone marrow biopsy assisted in making the correct diagnosis. She also later grew MAC from blood and sputum cultures. There were no other factors identified after a complete workup to explain DIC in this patient. After commencement of appropriate MAC therapy, she initially had a good response with some improvement of her coagulation parameters. Few months later, however, probably attributable to poor medication compliance, her condition deteriorated with development of thromboembolism, full-fledged DIC, sepsis, and an eventual fatal outcome. This case illustrates the importance of including disseminated MAC in the differential diagnosis of DIC in an AIDS patient.